Terahertz Absorption Characteristics of Multiwalled Carbon Nanotube Aqueous Dispersion Measured by Microfluidic Technique - Li, Yuchai; Qian, Siyu; Zhou, Hangyu; Jiang, Huimin; Wang, Xue; Su, Bo; Zhang, Cunlin (International Journal of Optics, 2022)
Multiwalled carbon nanotubes (MWCNTs) have excellent electronic, mechanical, and structural characteristics; however, their poor dispersion structure and large aggregates severely inhibit their function. A stable MWCNT dispersion in an aqueous solvent has been realized via ultrasonic dispersion and surfactant modification, providing a reference for improving MWCNT dispersion in various materials and solvents. In this study, a cyclic olefin copolymer with high transmittance to terahertz (THz) waves is used to prepare microfluidic chips. Then, the microfluidic and THz technologies are combined to study the THz absorption characteristics of MWCNT aqueous dispersion under different electric field (EF) intensities, magnetic field (MF) intensities, and MF action time. The results show that the THz spectral intensity of MWCNT aqueous dispersion decreases and the absorption coefficient increases with the increase of EF intensity, MF intensity, and MF action time. This phenomenon is explained from a microscopic perspective. The combination of microfluidic and THz technologies provides technical support for studying the characteristics of MWCNT aqueous dispersion and lays a foundation for elucidating the molecular microstructure of MWCNT aqueous dispersion.